Body composition evolution in elite football referees; an eleven-years retrospective study - Casajus, J. A.; Gonzalez-Aguero, A. (International Journal of Sports Medicine, 2015)
Fitness, and specifically body composition of football referees requires attention in order to achieve the highest possible standards. The aim of the present study was to describe body composition of elite Spanish football referees over 11 years. Data from 2001 to 2012 pre-seasons were analyzed from a total of 470 referees of 1st and 2nd categories in Spanish male football (1C and 2C respectively). Body mass index (BMI), sum of 6 skinfolds (6SS) and percentage of body fat (%BF) were assessed. 2-independent samples Student`s t-test between categories, and ANOVA tests with Bonferroni post-hoc analyses among seasons were applied. Overall, 1C referees were older than 2C in every season, and both 1C and 2C showed a decrease in 6SS, BMI and %BF throughout seasons (all p<0.05; from 82.5 to 62.9?mm, from 23.7 to 22.4?kg/m2 and from 13.7 to 11.7%). No differences were observed between categories in any season. Since football referees at the highest levels need to have a low %BF for the intense matches nowadays, an improvement in their body composition profile has been observed in a highly competitive league as `La Liga` in Spain over the last decade.